Maracatu: ritmos Sagrados - Eugenia de Freitas Maakaroun (2005)
Maracatu Ritmos Sagrados is a documentary that shows the reality of the Maracatus from Pernambuco. How they live and their masters, their queens, their world, their faces, their lives The ancestral souls of the afro-brazilian percussion are on the hills of Recife, Olinda and Nazaré da Mata. The human transforms on sacred, through therhythm, the dance and the colors. All of that reflect on image of the peregrine soul. The culture is insert on the day by day, on the streets, in the cities and at the history of the Brazilian people